Desempenho de sementes de milho tratadas com inseticida, fungicida e nematicida durante o armazenamento - Magalhães, Mario Flavio (2012)
The products to be applied in seed treatment must provide sufficient protection to both seed and seedlings in the field, keeping the fungi, insects and nematodes properly controlled. The aim of this study was to evaluate the possible immediate and latent effect of the product Avicta Complete (fungicide, insecticide and nematicide), Cruiser 350 FS + Maxim Advanced and Maxim Advanced on the physiological quality of hybrid maize seed. We used seven hybrids from Monsanto: DKB 330, DKB 350, DKB 390, AG 7000, AG 8021, AG 8015 and AG 9010. Seeds were subjected to the following treatments 1) Control, 2) Avicta Complete®, 3) Cruiser 350 FS® + Maxim advanced®, 4) Maxim Advanced®, and then stored at room temperature for up to 360 days. The assessments were made at 45, 90, 180 and 360 days, and the attributes evaluated were: germination, accelerated aging, speed of emergence and cold test. The data was analyzed according to statistical analysis on the effect of isolated products and the interaction treatment/storage in which the following conclusions were obtained: 1) The treatment on the seeds varies according to the hybrid; 2) In general the phytotoxic effect of the seed treatment is detected after 90 days in ambient storage of the seeds; 3) The fungicide Maxim Advanced did not result in any phytotoxic effect in the hybrids during storage in a not climacteric environment and 4) Corn seed storage for 360 days at cold conditions and treated with Avicta completo and Cruiser plus Maxim Advanced, remain with high physiological quality.